2009
DOI: 10.1194/jlr.m900177-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of recombinant liver fatty acid binding protein's antioxidant activity

Abstract: discovered by Ockner et al. in 1972 ( 2 ) and was originally named Z-protein. Since that time, there has been an explosive growth in information regarding the role of L-FABP in cellular homeostasis. While FABPs are present in many tissues, such as heart, brain, intestinal, skin, adipose, muscle, epidermal, ileal, myelin, and testis, L-FABP is found in abundance in hepatocytes where it accounts for ‫ف‬ 2% of the total cellular protein. Although L-FABP is abundant in the liver, it also is present in tissues suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 54 publications
(52 reference statements)
1
51
0
Order By: Relevance
“…In addition, L-FABP can bind PUFAs and therefore modulate the availability of these FA to intracellular oxidative pathways ( 52 ). In summary, these data suggest that loss of the primary lipid binding protein in hepatocytes renders FAs freely available for oxidation in systems containing high levels of ROS, including ALD.…”
Section: Ethanol Ingestion Alters Transcription Factor Activitymentioning
confidence: 91%
“…In addition, L-FABP can bind PUFAs and therefore modulate the availability of these FA to intracellular oxidative pathways ( 52 ). In summary, these data suggest that loss of the primary lipid binding protein in hepatocytes renders FAs freely available for oxidation in systems containing high levels of ROS, including ALD.…”
Section: Ethanol Ingestion Alters Transcription Factor Activitymentioning
confidence: 91%
“…The recent study showed that L-FABP has greater hydrophilic antioxidative activity than lipophilic antioxidative activity. 26 These findings indicate that the hydrophilic antioxidative effect of tubular L-FABP in PTCs attenuates AngII-induced SSHT via prevention of AngII-induced ROS generation. Indeed, the present in vitro study demonstrated that AngII-induced intracellular O 2 − generation was significantly attenuated in mProx-L. Interestingly, even rhL-FABP also attenuated the O 2 − generation in mProx as same as mProx-L, suggesting that not only endogenous but also exogenous L-FABP may have hydrophilic antioxidative effect under AngII stimulation.…”
mentioning
confidence: 72%
“…25 AngII increases generation of hydrophobic ROS, such as superoxide anion (O 2 − ) and hydrogen peroxide via the action of nicotinamide adenine dinucleotide phosphate oxidase. 23 The antioxidant activity of L-FABP is thought to result from the inactivation of free radicals by methionine and cysteine amino acids in L-FABP and also by exposure of the L-FABP-binding site to lipid peroxides, 26 indicating that L-FABP has both hydrophilic and lipophilic antioxidant effects. The recent study showed that L-FABP has greater hydrophilic antioxidative activity than lipophilic antioxidative activity.…”
Section: Discussionmentioning
confidence: 99%
“…AAPH is known to be a hydrophilic radical generator and AMVN is known to be a lipophilic radical generator 19 . Here, the radical scavenging activity of Toc at 40 ppm was equivalent to EGCg at 25 ppm, GTE at 23 ppm, Qu at 25 ppm, and RTE at 44 ppm, as described in Section 2.4.…”
Section: Figmentioning
confidence: 99%